HUBUNGAN DUKUNGAN SOSIAL DAN PENYESUAIAN DIRI PADA MASA PENSIUN PEJABAT STRUKTURAL DI PEMERINTAHAN PROVINSI BALI - Biya, Cokorda Istri Mirah Jayanti; Suarya, Luh Made Karisma Sukmayanti (Jurnal Psikologi Udayana, 2016)
Personal adjustment is an important factor for retirees. Adjustment is kind of behavior that aims to respond the individual needs. The purpose of personal adjustment is to obtain well becoming between personal demand and the environment where the individual lives. In order to get better personal adjustment in retirement, it really needs social support. Social support refers to provide comfort, taking care and appreciating. The structural officer is identical with adequate service facility, the presence of assistants, the relations and high income, which is cause the relationship between social support and personal adjustment in retirement is highly visible on the structural officer of Civil Servants (PNS) in Bali Province Government who has retired already. This research aims to determine the relationship between social support and personal adjustment in the retirement of structural officer. The subject of this research is structural officer who has retired already and worked in Bali Province, age range is 57-58 years old. Total subjects in this study is 105 persons. Reliability of social support scale is 0.910 and the reliability of retirement personal adjustment scale is 0.894. Normality of social support is 0.200 and normality of personal adjustment in retirement variable is 0.052. Linearity test is 0.000. Analysis methods in this research is pearson product moment correlation . The result of correlation test is 0.717(p=0.000). Based on the result, it shows that there is relationship between social support and personal adjustment in the sstructural civil servants of government in Bali Province. Its mean the higher the sosial support, the higher the adjustment to retirement.Keywords: social support, personal adjustment, retirement